Antimicrobial activity of levofloxacin – M33 peptide conjugation or combination. Issue 2 (30th November 2015) - Ceccherini, Federica; Falciani, Chiara; Onori, Martina; Scali, Silvia; Pollini, Simona; Rossolini, Gian Maria; Bracci, Luisa; Pini, Alessandro
Abstract : M33 is a branched antimicrobial peptide against Gram-negative bacteria. We reported its conjugation with levofloxacin and its antibacterial activity. Abstract : M33 is a branched peptide currently under preclinical characterization for development as a new drug against Gram-negative bacteria. Here we report its antibacterial activity in conjugation or combination with levofloxacin (LVFX), a fluoroquinolone antibiotic. Antibacterial assays showed no significant differences in activity when used in conjugation, while the combination of M33 and LVFX showed improved activity against Gram-negative bacteria. Combination treatment therefore opposes antimicrobial-resistance, restoring the effect of LVFX.